CONCEPT, ESSENCE AND PRINCIPLES OF ADMINISTRATIVE SERVICE PROVISION BY PUBLIC AUTHORITIES IN UKRAINE - Prokopenko, Sergii (Public Management and Policy, 2025)
The formation of the theoretical framework of the phenomenon of administrative services is updated against the background of active processes of decentralization and development of administrative reform in Ukraine. The purpose of the study is to analyze the definition of “administrative services”, its essence and the principles of providing administrative services by public authorities. The article deals with the essential features of the phenomenon under study, types and approaches to the provision of administrative services in the context of practice in Ukraine. The study analyzes the key positions of modern scholars on the issues outlined, the national legislative field provides its own considerations and proposals for optimization changes. It has been found that, against the background of the diversity of existing definitions (“management services”, “public services”, “public-power services”, etc.), all existing definitions are characterized by non-property expression, specific nature and targeted orientation to satisfy the client. It is substantiated that the specificity of administrative services is the presence of a powerful subject of their provision, and the vector of relationships that arise in this case is to meet the legitimate needs of a person, the protection of his interests and rights. The basic principles of administrative services in Ukraine which are enshrined in the regulatory field. It is found out that the current scientific position actualizes the “service” nature of the provision of administrative services. The shortcomings of the generally accepted version of the definition of “administrative services”, including the lack of a meaningful category of focus on satisfying the legitimate interests of a person and the guarantees of the realization of his fundamental rights, were noted. The results of the study emphasize the need to minimize the intervention of public authorities in the person's personal living space, expand the functionality of “service” and ensure the quality of administrative services.